Proposta de um modelo teórico para o ensino de texto dissertativo-argumentativo para alunos do Ensino Médio: um enfoque da Linguística Sistêmico-Funcional - Silva, Maria Piedade Teodoro da (2017)
The purpose of this thesis is the delineation of a diagnosis based on the examination of the unit of structure and texture of the argumentative-dissertative essay (ADTs), written by High School students and the ones in preparatory course. In light of the recent literature on the production of this type of text, mapping the areas of mismatch between the suggestions of this literature on the ADT and the effective accomplishment of this type of text by the candidate. The diagnosis should allow the development of a framework that provides teachers with resources that can guide students to write texts that meet the expectations of the academic audience in terms of both structure and language requirements. The difficulty that writing production represents for most students, at all levels of education, is present in the discourse of teachers from the most divergent areas. As for the high school students, as well as the university ones, this difficulty relies on the writing of ADT - the type of text requested for the students, but in which they, according to research, find it difficult to argue, discuss and persuade. For the executive secretary of MEC, Maria Helena Guimarães de Castro, the writing relates to the language performance. With the basic support of Systemic Functional Linguistics - a multiperspective model, designed to give analysts complementary lenses for the interpretation of the language in use. This thesis examines interpersonal aspects related to gender structure - with its stages and purposes, as well as the texture of the ADT, focusing on the lexicalgrammatical choices of the text (cohesion, coherence, modality and evaluation). The research should answer the following questions: (a) What are the interpersonal resources that affect the success of producing an ADT? (b) What role does the gender structure unit play in this issue? and the texture unit? The diagnosis should allow the development of a framework that provides teachers with resources that can guide students to write texts that meet the expectations of the academic audience in terms of both structure and language requirements